2017
DOI: 10.3389/fgene.2017.00014
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Relationship between Alternative Splicing and Gene Duplication

Abstract: The protein diversity that exists today has resulted from various evolutionary processes. It is well known that gene duplication (GD) along with the accumulation of mutations are responsible, among other factors, for an increase in the number of different proteins. The gene structure in eukaryotes requires the removal of non-coding sequences, introns, to produce mature mRNAs. This process, known as cis-splicing, referred to here as splicing, is regulated by several factors which can lead to numerous splicing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 54 publications
(55 reference statements)
3
51
1
Order By: Relevance
“…Interestingly, we observed that a paralog of U2AF2 on LG 33 was differentially expressed between ecotypes. This suggests that paralogs, which potentially originated through the whole-genome duplication in salmonids (Lien et al 2016), might be regulated through different molecular processes, thus increasing functional diversity while minimising constraints (Bush et al 2017;Iñiguez and Hernández 2017). A similar pattern was observed for MYH.…”
Section: Alternative Splicing and Gene Expression Have Contrasting Phmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, we observed that a paralog of U2AF2 on LG 33 was differentially expressed between ecotypes. This suggests that paralogs, which potentially originated through the whole-genome duplication in salmonids (Lien et al 2016), might be regulated through different molecular processes, thus increasing functional diversity while minimising constraints (Bush et al 2017;Iñiguez and Hernández 2017). A similar pattern was observed for MYH.…”
Section: Alternative Splicing and Gene Expression Have Contrasting Phmentioning
confidence: 81%
“…A similar pattern was observed for MYH. However, more analyses are needed to test this pattern (Iñiguez and Hernández 2017) and assess the role of the whole-genome duplication in salmonids on the regulatory divergence between recently diverged ecotypes. Without detailed molecular studies of translation, protein abundance and transcript decay for candidate genes, we cannot discern the exact molecular and phenotypic impact of splicing and expression events (Mallarino et al 2017).…”
Section: Alternative Splicing and Gene Expression Have Contrasting Phmentioning
confidence: 99%
“…Finally, DTU was compared between genes with a different number of paralogs to study the relationship between gene duplication and DTU. The relationship between gene duplication and AS has been studied extensively, but is not fully understood (Iniguez and Hernandez, ). Singleton genes in rice were found to produce less alternatively spliced isoforms than genes with paralogs (Lin et al ., ), but for human genes the reverse trend was observed (Roux and Robinson‐Rechavi, ).…”
Section: Resultsmentioning
confidence: 99%
“…Full enrichment results can be found in Table S3. studied extensively, but is not fully understood (Iniguez and Hernandez, 2017). Singleton genes in rice were found to produce less alternatively spliced isoforms than genes with paralogs (Lin et al, 2008), but for human genes the reverse trend was observed (Roux and Robinson-Rechavi, 2011).…”
Section: Cds Altering Dtu Occurs Disproportionately Across Genes Withmentioning
confidence: 99%
“…Cells can generate multiple messenger RNAs (mRNAs) with different functions from a single genomic gene through alternative splicing [29], [30]. Types of alternative splicing include the use of alternative 5′ splice sites (alternative donor), alternative 3′ splice sites (alternative acceptor AA), exon skipping, intron retention and mutually exclusive exons (Figure 2) [31]. In addition, new discoveries have shed light into the mechanisms responsible for the production of circular RNAs (circRNAs), which imply alternative splicing [32]-[34].…”
Section: B-splicingmentioning
confidence: 99%